Qualitative exploration of the experiences and perceptions of diet in psoriasis management among UK adults - Sarah Mason; Poppy Hawkins; Kate Earl; Rosalind Fallaize; Thanasis G Tektonidis (BMJ Open)
Objective This study aimed to explore the use, experiences and perceptions of diet in psoriasis management among adults with lived experience in the UK.Design Qualitative. Data were analysed thematically using a reflexive thematic approach.Setting Online discussions with adults living with psoriasis in the UK.Participants Nine adults (two men, seven women) ≥18 years of age, living in the UK, English speaking, with a diagnosis of psoriasis of any severity.Results Four key themes were generated: (1) impact of diet, (2) dietary modification, (3) dietary information and (4) dietary support. Overall, the majority (n=8) perceived that diet had an impact on their psoriasis. Most participants (n=7) reported trying restrictive diets including dairy free, gluten free and ‘cleanses’ to help manage their psoriasis with limited success. A perceived lack of dietary support resulted in participants relying on social media and online forums for dietary information. Participants reported a high cognitive burden due to the lack of reliable nutrition guidance and insufficient dietary support from healthcare professionals (HCPs).Conclusions Participants rely on social media and online forums for dietary information, which suggest unsubstantiated restrictive diets that could negatively impact health. Participants felt overwhelmed by dietary recommendations and wanted more relevant dietary support. In the absence of evidence-based dietary information for psoriasis, HCPs need to be able to provide basic dietary support and combat misinformation. Larger studies aimed at understanding how best to support people with psoriasis are needed.